EP1046 Living life in the face of loss: parenteral nutrition in ovarian cancer patients in bowel obstruction. (1st November 2019) - Sowerbutts, AM; Lal, S; Sremanakova, J; Clamp, A; Jayson, GC; Teubner, A; Todd, C; Raftery, A M; Sutton, E; Burden, S
Abstract : Introduction/Background: Malignant bowel obstruction (MBO) is a complication of advanced ovarian cancer and these patients may receive home parenteral nutrition (HPN). This study investigates patients' and relatives' experiences of HPN, alongside patients' nutritional status and survival outcomes. Methodology: A mixed methods study involving 38 patients with ovarian cancer in MBO admitted to a tertiary referral hospital over 15 months. Data on nutritional status, body composition, and patient characteristics were collected from patients' notes and computerised tomography scans. In addition, seventy-five longitudinal in-depth interviews were conducted with 20 patients considered for HPN, their relatives and healthcare professionals. Interviews were transcribed verbatim and analysed thematically influenced by the techniques of Van Manen Results: Of the 38 women, 32 received parenteral nutrition in hospital and 17 were discharged on HPN. Nutritional status was poor with 31 of 33 women who had a CT scan having low muscle mass, although 10 were obese. Median overall survival from admission with MBO for all 38 women was 70 days (range 8–506) and for those 17 on HPN was 156 days (range 46–506). Patients experienced HPN as one facet of their illness, but viewed it as a 'lifeline' that allowed them to live outside hospital. Nevertheless, HPN came with losses including erosion of normality through an impact on activities of daily living and dealing with the bureaucracy surrounding the process. Relatives coped but were often left in an emotionally vulnerable state. Conclusion: Patients and relatives recognised HPN as a 'lifeline' and were grateful for it. However this benefit came with losses and healthcare professionals need to be realistic about these and aware of relatives' needs. Nevertheless, patients are prepared to suffer losses in order to continue living. Disclosure: Nothing to disclose